Pengaruh Kepemilikan Keluarga dan Leverage terhadap Kinerja Perusahaan - Sherly Prastia; Afriyanti Hasanah (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
This study aims to examine the effect of family ownership and leverage on company performance in the 2017-2019 period. The population of this study are all manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The company's performance in this study is calculated using the Altman Z-Score. Samples were taken using purposive sampling method and obtained 35 companies as samples in this study. The method used in this study uses Multiple Linear Regression using Eviews version 10. The results of this study indicate that family ownership has no significant positive effect on company performance. Meanwhile, leverage has a significant negative effect on company performance.